Accurate calculation of the slip factor of axial cascades and impellers for arbitrary blade shapes - Smith, Henrik; Semel, Matthias; Epple, Philipp; Bleiziffer, Mihai; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2011)
Nowadays, design, redraft and optimisation strategies of axial fans often still rely on the one dimensional mean line theory. However, as it is well known, it is based on a number of assumptions that do not apply to real flow behaviour so that various deviations can be observed. In the present paper, the plane potential theory is used to examine and calculate these deviations. The behaviour of axial cascades is analysed in general and a slip factor is computed. On this basis a quasi-3D calculation method is developed. It is applied to an exemplary impeller and the results are compared with 3D CFD computations. The main characteristic figures are presented and different angle correction and angle exaggeration methods are investigated and compared. Finally, the applicability of the presented method to a precise axial fan design process is illustrated. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.accura

Adapting a high-speed train to winter in Russia. Simulation helps prevent traction problems for rail travel during extreme weather conditions - Epple, Philipp; Becker, Stefan; Ilic, Caslav; Karic, Branimir; Ali, Irfan; Delgado, Antonio (ANSYS Advantage, 2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.ITC.stmmec.adapti

A design method of radial fans considering the torque-speed-characteristic of the motor - Epple, Philipp; Miclea, Mihai; Pfannschmidt, Klaus; Grobeis, Detlev; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2010)
The use of high speed radial impellers is very common in fans for industrial applications. The most common design case is the one with constant speed. In that case, one assigns the corresponding value to the speed n, hence the speed no longer matters in the further design procedure: it is given and it is constant. However, in many cases the speed is not constant, since it is governed by the torque-speed characteristic of the driving motor. In such a case it is necessary to consider the motor characteristic already at the design stage. In the present work a design method was developed in order to perfectly match the torque-speed characteristic of the radial impeller to the torque-speed characteristic of the driving motor. In such a way it is possible to design an impeller-motor unit with maximum efficiency. The extended impeller mean-line-design formulas presented in Epple [6] were complemented with the equations describing the motor torque-speed-characteristic. Both sets of equations where combined and solved in order to achieve a prescribed operating range at a maximum efficiency. In order to validate the design method, it was applied to an industrial fan which should be improved. That radial fan with spiral casing consisted of the main radial fan and a motor cooling axial fan at the other end of the shaft. This later fan was rotating at a too low speed leading to cooling problems of the motor. Hence, a new fan had to be designed which had to deliver the same hydraulic performance but at higher rotating speeds. This had to be done, however, on the given motor. That could only be done when properly designing an impeller matching its torque-speed characteristic to the torque-speed characteristic of the motor: it was an excellent task to validate the combined impeller-motor design procedure. Under these constrains six designs where performed and validated with a commercial CFD solver. The three best designs according to the CFD results were built as prototypes and measured at a standard test rig. The best design delivered the prescribed head-flow characteristic at an even improved hydraulic efficiency. The higher speed was also properly achieved. The design procedure is described and explained in detail and a detailed CFD analysis is presented, complemented by the experimental data obtained at the test rig. A final comparative analysis of the combined impeller-motor design method, the CFD analysis and the measurements is presented. Copyright © 2010 by ASME.
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.adesig
Keywords: CFD; Impeller-motor matching; Radial impeller design; Test rig measurements; Torque-speed-characteristic

Analysis of propeller design methods and validation with the CFD computation of a propeller-pump - Albert, Sven; Epple, Philipp; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2012)
There is a large variety of axial propellers available, ranging from very small devices with only millimeters in diameter to ship propellers being several meters in size. Also they are applicable in several different ways, from low pressure propellers when actually used as fans or high pressure differences when used for propulsion purposes. Several theories have been developed to calculate and predict propeller performance. The basic theory is the linear momentum theory which takes only the axial motion into account. The theory can be refined taking the rotational motion and hence the angular momentum into account and also segmenting the propeller into several blade elements, to which classical airfoil theory can be applied. However, common literature does not include any precise verification of these theories. The present work shows with CFD computations the validation and hence accuracy of the blade element theory and its predecessors on a specific axial machine, namely the blood assist Reitan catheter propeller - pump. The propeller - pump is evaluated in a large operational range, using a commercial CFD code. The theory is then applied to the CFD results calculating the stream tube, in which all the necessary parameters, like interference factors, are evaluated. Those will deliver the machine characteristics thrust, torque and efficiency according to these theories. Comparison of this data to the CFD values shows good agreement, especially when segmenting the propeller and therefore using multiple stream tubes. Thus, the validity of these theories and its range of applicability was verified showing in detail how these theories can be employed as reliable design tools coupled with CFD verification. Copyright © 2012 by ASME.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.analys

Analytical and numerical investigation of the fluid structure interaction of an elastic beam in a water channel - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2020)
The interaction between fluids and solids is becoming increasingly important in the design and analysis of machines, buildings and systems. Due to the fluid-mechanical phenomenon of turbulence and the associated flow and vortex shedding, the fluid structure interaction must be considered, for example, in aircraft wings, civil engineering (e. g. television towers or bridges), the rotor blades of wind turbines or in the field of sensor technology. Due to the increasing computing power, increasingly complex tasks can be calculated with the help of numerical simulations. In this paper, an elastic beam has been defined as test case and has been analyzed in different ways with the methods of the fluid structure interaction (FSI), i.e. with analytical and numerical approaches. For this purpose, the plastic beam has been fixed on one side in a water channel and the flow around it and the beam deflection have been measured. The deformation of the beam due to the flow load around it has been analyzed for varied flow velocities. First, the beam deformation has been estimated based on the analytical equations from structural mechanics and an assumed stagnation pressure on the beam surface. Additionally, the drag coefficient from experimental data of the literature was used to estimate the force on and the bending of the beam. Then two numerical simulations with different FSI coupling methods have been performed with Ansys Workbench 2020 R1. On the one hand, a one-way coupling analysis has been performed in which the pressure field was calculated from the CFD simulation and then transferred to the mechanical analysis. On the other hand, a two-way coupling computation has been performed, which also takes transient effects into account. For this purpose, the flow field and the pressure field have been exchanged iteratively between the fluid and the mechanical solver. This coupling approach is general and corresponds to reality since large deformations and non-linearities are considered. However, this approach always requires a very computation intensive, nonstationary calculation. The results obtained from these parameter studies have then been evaluated and compared in order to determine the accuracy of each analysis methodology. The elaborated results have been discussed and analyzed in detail.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Beam deflection; Fluid-Structure-Interaction; FSI

Analytical and numerical investigation of the optimum pressure distribution along a low-pressure axial fan blade - Pascu, Maria; Miclea, Mihai; Epple, Philipp; Delgado, Antonio; Durst, Franz (Proceedings of the Institution of Mechanical Engineers Part C-Journal of Mechanical Engineering Science, 2009)
In the field of axial flow turbomachines, the two-dimensional cascade model is often used experimentally or numerically to investigate fundamental flow characteristics and overall performance of the impeller. The core of the present work is a design method for axial fan cascades aiming to derive inversely the optimum blade shape based on the requirements of the impeller and not using any predefined aerofoil profiles. While most design strategies based on the aerofoil theory assume constant total pressure at all streamlines, i.e. free-vortex flow, this paper investigates the possibility of varying the total pressure along the blade and based on that, an analytical expression of the outlet blade angle is determined. When computing the blade profile at a specified radius, critical parameters reflecting on the flow characteristics are observed and adjusted (i.e. sufficient lift and controlled deceleration of the flow on the contour) so that the resulting profile is derived for minimum losses. The validation of this design strategy is given by the numerical results obtained when employed as an optimization tool for an industrial fan: 10-20 per cent absolute increase in the static efficiency of the optimized impeller. © IMechE 200
UnivIS-Import:2015-04-14:Pub.2009.tech.ITC.stmmec.analyt
Keywords: Blade profile; Design strategy; Non-free-vortex flow; Optimum pressure distribution

Analytical model for deformable roll coating with nip feed - Grashof, Bettina; Epple, Philipp; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2012)
UnivIS-Import:2015-10-26:Pub.2012.tech.ITC.stmmec.analyt_3

An analytical and computational investigation of room heating due to complex geometry heat sources - Friedrich, Fabian; Epple, Philipp; Steber, Michael; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2015)
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.ananal
Keywords: Characteristic length; Grashof Number; Heat transfer; Heat transfer coefficient; Natural convection; Nusselt number; Rayleigh number

An extended analytical and numerical design method with applications of radial fans - Epple, Philipp; Miclea, Mihai; Luschmann, Christian; Ilic, Caslav; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings, 2009)
The use of high speed radial impellers is very common in fans for industrial application. It is very common also to manufacture the radial impellers for these fans with circular arc blades. The design process is also almost always based on former impeller series and experimental data available. In this work a method is presented to improve the efficiency of radial impellers with a combined analytical and numerical method. This method is based on a new extended analytical formulation of the flow in radial impellers allowing optimizing efficiency in design stage. The blade shapes are computed with an inverse method. The design is then validated by means of CFD computation. Finally a prototype was built and measurements were carried out in a test rig. It is shown also that the design method delivered very good predictions leading to an efficiency increase of 13% of efficiency and a maximum flow rate increase of 11% absolute. The design point was also met. It is also shown that the numerical computations and measurements are in good agreement. An analysis of the CFD results is also presented, giving insight in the substantial flow information inside the old and the new impeller. The method presented is a combined analytical and numerical method suited to design high efficiency radial impellers without the need of a previous impeller series or knowledge of experimental data. Copyright © 2010 by ASME.
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.anexte

Application of an inverse cascade analytical and numerical design method used in the design of axial fans - Bleiziffer, Mihai; Epple, Philipp; Smith, Henrik; Semel, Matthias; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2011)
This contribution presents an inverse design method for axial flow fans validated by 3-D RANS numerical simulations. It is based on an analytical performance derivation for different free-vortex distributions combined with a mean-line pre-design tool and supported by a new 2-D cascade potential flow computational method. This computes the 2-D planar cascade flow field and the inviscid deflection angle of thin arbitrary shape airfoils at different machine radii followed by a numerical radial integration into a quasi-3-D method. For validation, several fan designs were investigated, showing the influence of important design parameters as well as the potential of the present method by redrafting an industrial fan. The 2-D planar potential cascade code was validated against the Weinig's coefficient diagram for flat plate and circular arc cascades. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.applic

Asymptotic analysis of flow processes at drawing of single optical microfibres - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (International Journal of Chemical Reactor Engineering, 2011)
Microstructured optical fibres (i.e. fibres that contain holes) have assumed a high profile in recent years, and given rise to many novel optical devices. The problem of manufacturing such fibres by heating and then drawing a preform is considered for both the cases of annular microfibres and annular capillaries. A fluid-mechanics model suggested in literature that uses asymptotic analysis based on the small aspect ratio of capillaries is analysed and revised. The leading-order equations are examined in some asymptotic limits, many of which give valuable practical information about the control parameters that influence the drawing process. Additionally, the solution obtained for a single capillary provides a suitable basis for describing more complicated fibre structures. Copyright © 2011 The Berkeley Electronic Press. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.asympt
Keywords: asymptotic analysis; holey fibre; microstructured optical fibres; numerical efforts; photonic crystal fibres

A theoretical derivation of the Cordier diagram for turbomachines - Epple, Philipp; Durst, Franz; Delgado, Antonio (Proceedings of the Institution of Mechanical Engineers Part C-Journal of Mechanical Engineering Science, 2011)
The design of high-efficiency fans is often based on the experience of the designer. In order to determine its main dimensions, fan designers use the Cordier diagram. For a given operating point (i.e. flowrate and pressure, and a rotating speed), the optimum diameter of high-efficiency fans can be found in the Cordier diagram. The Cordier diagram is an empirical diagram based on measurements. It delivers a relation between flowrate, pressure, rotating speed, and diameter. However, the Cordier diagram does not provide any information on the blade shape (i.e. the angles and the blade width). In order to fill this gap, there are design rules based on the experience of the designer and some analytical performance parameters in the literature. One very common performance parameter is the reaction, which is the ratio between the static and the total pressure rising from the impeller inlet to its outlet. These design rules and performance parameters are, however, of limited use. Therefore, the total-to-static ideal efficiency is introduced to yield, together with the speed and diameter numbers σ and δ, the essential parameters that distinguish the different turbomachines in the Cordier diagram. Based on the integral parameters of the flow and the geometry of turbomachines, a performance analysis of turbomachines is performed and the Cordier diagram is theoretically derived.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.atheor
Keywords: axial impeller; blowers; computational fluid dynamics; Cordier diagram; fans; integrated performance optimization; inverse design method; mean line analysis; performance analysis; radial impeller; turbomachinery

CFD analyses and design of a turbocompound system - Vogel, Thomas; Epple, Philipp; Hermann, Andreas; Grashof, Bettina; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2013)
In a turbocompound (TC) system a turbocharged engine is coupled with an additional power turbine, which recovers exergy of the exhaust gas after the turbocharger. The gained power is added to the engine power by a gearbox and a hydrodynamic coupling. The benefit of turbocompound is that the efficiency of internal combustion engines is improved substantially.The challenge with turbocompounding is that a high speed turbine is coupled with a slow speed engine. Through the transient requirements in mobile applications the operating points of the engine are variable while the turbo machine is designed for a continuous and steady flow. Matching the components is an additional challenge in designing the flow path of a TC System. A systematic approach in which the flow path is divided into three regions is applied: the interstage duct, the power turbine consisting of the rotor and its guide vane as well as the exhaust gas collector. After defining performance criteria for the individual regions, they are analysed by computational fluid dynamics (CFD). For this purpose, the model for the CFD-simulation is validated with measurements. For the interstage duct the influence of the mass flow and the outlet swirl of the turbocharger are analysed. For the exhaust gas collector the influence of the outlet swirl and mass flow from the power turbine is evaluated by a sensitivity study. Based on verified CFD simulations as well as analytical considerations it was possible to show that an improvement of the turbine performance is still possible. Parameters to be optimized were identified. As a result of the study an improved method for high efficiency aerodynamic design of turbocompound systems was developed. Based on this method the parts of the TC system were aerodynamically optimized. The performance of the new design was verified by CFD. Improvements in the power output up to 10% were achieved in stationary engine points. Copyright © 2013 by ASME.
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.cfdana

CFD computation, analysis and design of a two-bladed wastewater pump - Litfin, Oliver; Mohr, Christian; Haddad, Kais; Epple, Philipp; Semel, Matthias; Becker, Klaus; Klein, Horst; Delgado, Antonio (ASME 2011 International Mechanical Engineering Congress and Exposition (IMECE 2011), 2011)
In this work a wastewater pump with a two-bladed prototype impeller and a specific speed of 0.68, referring to a wellestablished industrial design, was simulated in a commercial CFD solver, ANSYS CFX. Simulations of the impeller only and of the complete pump with spiral casing including a detailed analysis of the flow patterns were performed. A parameter study with around 25 new designs containing variations of the inlet angle and the wrap angle was carried out, leading to significant improvements of the flow pattern as well as of the hydraulic efficiency. Based on the optimum leading edge and wrap angle, the total head was improved by variation of the exit blade angle. Having set the better main dimensions, the effect of the blade shape, i.e. blade angle distribution, was investigated. Here it is shown that changing the blade angle distribution in such a way that the point of maximum blade angle is shifted to a bigger radius can lead to substantial improvements. One special focus in this whole study was also to describe and control the behavior of the relative eddy, which is directly related also to the slip factor. In the scope of this work it is shown how it is possible to influence and move the relative eddy to the best position, since due to the small relative velocities in the blade passage it is impossible to fully avoid it. A detailed analysis of these CFD results is presented as well as the recommendations for an efficient design of this special type of wastewater pump impellers. Copyright © 2011 by ASME.
UnivIS-Import:2017-11-07:Pub.2011.tech.ITC.stmmec.cfdcom

Combined impeller-diffuser design and the influence of slotted guide vanes on the performance of radial diffusers - Epple, Philipp; Miclea, Mihai; Ilic, Caslav; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.combin

Compact test rig design for fans and blowers - Epple, Philipp; Semel, Matthias; Grashof, Bettina; Delgado, Antonio (Proceedings of ASME International Mechanical Engineering Congress and Exposition, 2014)
In order to develop high efficiency fans and blowers the design methods are being improved continuously. The same is valid for the modern CFD (Computational Fluid Dynamics) programs, which are used in the design process in order to validate the designs. However, at the end of the development process measurements at test rigs are needed in order to verify the final design. CFD is substituting to some extend EFD (Experimental Fluid Dynamics), but still EFD is the final way to evaluate a design. Usually the universities and the industry have some test rig where measurements are done. These test rigs in general are unique and built according to a corresponding standard. However, these standards, as for example the German DIN 24 163 [1] or the European DIN EN ISO 5801 [2] prescribe only the main proportions of such test rigs while several important features are not described in detail. In particular the aerodynamic theory behind the standard is very often omitted. For example, the measurement of the pressure characteristic of a fan is performed at a pressure tab at the test chamber wall and not at the fan itself. How to assure that the pressure measured at the wall tab corresponds to the fan pressure? In this work the relevant theory behind the design of test rigs was worked out in detail for the relevant test rig features where the standards do not explain the fluid mechanical aspects. On this basis pressure and suction side test rigs were designed and completely simulated with a commercial CFD program, Ansys CFX. The goal was to develop compact test rigs according to the European DIN EN ISO 5801 [2] standard. It is shown in this work how the size of the test chamber influences the measuring results. Furthermore an in detail CFD study of a series of flow measurement devices, as inlet and Venturi nozzles, was performed. In such a way it was possible to show the influence of the dimensions of these devices on the accuracy of the measurements. Finally two test rigs were built, one for suction side and the other one for pressure side measurements. Compared to other test rigs in this category in use in the industry in Germany it was possible to reduce the size of these test rigs by a factor of about two complying with the measurement uncertainty of the DIN EN ISO 5801 standard.
UnivIS-Import:2015-07-08:Pub.2014.tech.ITC.stmmec.compac

Comparison between an analytical asymptotic fiber drawing model with full Navier-Stokes solution taking into account the effects of inner pressure and surface tension - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (Journal of Lightwave Technology, 2011)
A fluid-mechanics model that make use of asymptotic analysis based on small aspect ratio of capillaries has been compared with the full 3-D set of the N.-St. equations, for modelling the fabrication of capillary tubes. The final asymptotic equations are solved numerically and then compared with the N.-St. solutions, obtained with a commercial finite elements solver. The present paper focuses on the comparison of the solution of the two methods taking into account the effects of surface tension and internal hole pressure, since those are of essential importance during drawing. It is shown that the analytical asymptotic method delivers reliable results for practical applications, as long as the inner pressure or the temperature does not exceed too high values. © 2011 IEEE.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.compar
Keywords: Asymptotic analysis; holey fibres; mathematical modelling; microstructured optical fibres (MOFs); numerical methods; photonic crystal fibres

Design of radial impellers: A combined extended analytical and numerical method - Epple, Philipp; Karic, Branimir; Ilic, Caslav; Becker, Stefan; Durst, Franz; Delgado, Antonio (Journal of Mechanical Engineering Science, 2009)
The use of high-speed radial impellers is very common in blowers for industrial application. It is also very common to manufacture these impellers using circular arc blades. The design process as well is almost always based on former impeller series and experimental data available. In this work, a method is presented to improve the efficiency of radial impellers with a combined analytical and numerical method. This method is based on an extended analytical formulation of the flow in radial impellers, allowing optimizing efficiency in the design stage. It is complemented by the mathematical implementation of a well-known qualitative principle of efficiency optimization according to Carnot. Finally, the torque-speed characteristic of the motor is included in the design stage. The blade shapes are computed using an inverse method. The design is then validated by means of computational fluid dynamics (CFD) computation with a commercial solver. Finally, a prototype was built and measurements were carried out in a test rig. It is also shown that the design method provided very good predictions leading to an efficiency increase of 13 per cent and a maximum flowrate increase of 11 per cent. The design point was also met. It is also shown that the numerical computations and measurements are in good agreement. An analysis of the CFD results is also presented, giving an insight view into the substantial flow information within the old and the new impellers. The method presented is a combined analytical and numerical method suited to design high-efficiency radial impellers considering also the torque-speed characteristic of the motor without the need of a previous impeller series or knowledge of experimental data. © IMechE 2009.
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.design
Keywords: Computational fluid dynamics; Integrated performance optimization; Inverse design method; Mean line analysis; Radial impeller; Test rig measurements; Torque-speed characteristic

Development of a Measurement Method for the Classification and Performance Evaluation of Positive Pressure Ventilation (PPV) Fans - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (Proceedings of the ASME 2018 5th Joint US-European Fluids Engineering Division Summer Meeting. Volume 3: Fluid Machinery; Erosion, Slurry, Sedimentation; Experimental, Multiscale, and Numerical Methods for Multiphase Flows; Gas-Liquid, Gas-Solid, and Liquid-Solid Flows; Performance of Multiphase Flow Systems; Micro/Nano-Fluidics., 2018)
Positive Pressure Ventilation (PPV) fans are used by fire departments. The specified performance data differ depending on the manufacturer, as there is no international and commonly accepted standardized measuring method for evaluating the PPV fan performance. In the present work a new measurement method for the classification and performance evaluation of PPV fans is proposed. These fundamental investigations are based on numerical simulations and experimental test studies. The simulations have been performed with the commercial CFD software ANSYS CFX and the test measurements have been carried out on a newly developed test rig. For the predesign of the measurement method, the flow behavior of a free jet with swirl has been investigated with CFD simulations. A special feature of the PPV fans is that the generated flow rate is not only due to the flow through the rotating impeller, but also a significant flow rate is generated outside the PPV fan due to the viscous shear stresses (principle of a viscous jet pump). For the measurements a new test rig has been designed in order to measure the flow velocity of the PPV fan as it is in real firefighter’s fire combat situations. The new test rig design concept and the numerical and experimental results of these studies are presented in detail in this work.
Keywords: Fans; Performance evaluation; Pressure; Ventilation; Flow (Dynamics); Computational fluid dynamics; Engineering simulation; Impellers; Jet pumps; Shear stress; Warfare

Development of an experimental setup for double rotor HAWT investigation - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Epple, Philipp; Körbel, Wolfgang; Delgado, Antonio (Proceedings of ASME Turbo Expo 2012, 2012)
An experimental set-up was designed and constructed to study the performance of single and double rotor Horizontal Axis Wind Turbines (HAWT) configurations. Different tip speed ratios (TSR) were tested under varying wind loadings. The experimental study was carried out in order to investigate the HAWT performance and thereby increase its aerodynamics efficiency. Another setup was built to measure the torque rotational speed characteristic of the generator. The double rotor configuration was chosen intentionally to study the efficiency improvements when the second downstream rotor extracts the kinetic energy dismissed by the upstream rotor. The study showed that the power coefficient can be indeed increased about 50 % with a double rotor HAW T configuration, and the power gained from a counter rotating rotor is higher than that of a co-rotating rotor owing to the effect of the wake of the upstream rotor. In addition, a theoretical analysis of wake effect of the upstream rotor on the downstream rotor including the effect of the distance between the two rotors on the total power coefficient was made and investigated experimentally in order to estimate the optimum distance between the two rotors. Copyright © 2012 by ASME.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.develo_7

Exact solution of the plane flow and slip factor in arbitrary radial blade channels and extended design method for radial impellers - Hetzer, Tobias; Epple, Philipp; Delgado, Antonio (ASME 2010 International Mechanical Engineering Congress and Exposition, IMECE 2010, 2010)

EXACT SOLUTION OF THE PLANE FLOW AND SLIP FACTOR IN ARBITRARY RADIAL BLADE CHANNELS AND EXTENDED DESIGN METHOD FOR RADIAL IMPELLERS - Hetzer, Tobias; Epple, Philipp; Delgado, Antonio (2012)
Since the one dimensional mean line theory, sometimes complemented with calculations of slip factors and used for design of impellers usually leads to considerable deviations from reality the plane potential theory is used to get a better insight on the flow inside the impeller and to predict characteristic curves.Investigations presented here show that it is possible to calculate the exact solution of the plane flow and slip factor in arbitrary radial blade channels. This can be used in an extended design method for radial impellers which is suggested by the authors.

Extended mean line theory for axial fans - Analytic calculation of the flow characteristics for off-design points - Semel, Matthias; Epple, Philipp; Bleiziffer, Mihai; Delgado, Antonio; Smith, Henrik (Proceedings of the ASME Turbo Expo, 2011)
The use of axial fans is very common for industrial applications. The most common design case is the free vortex design. It ensures constant meridional velocity and hence an axisymmetric and two-dimensional flow. Those designs have proved to be robust and to deliver good results. However, the free vortex model holds only at the design point. At off-design points the flow characteristics differ substantially from the free vortex model, whereby the extent of validity of a forced vortex model is obtained. Solving the equation of radial equilibrium for off-design points enables a more precise design prediction considering the impact of the variable meridional velocity and the angular momentum. This approach can be applied to free vortex models as well as forced vortex models. In the present work theoretical formulas for the flow characteristics at off-design points were developed and implemented. Three angular momentum profiles, one free vortex and two forced vortex models, were analyzed relative to the change in the meridional velocity and angular momentum profiles. The impact of these modifications on the performance characteristics of axial fans, such as pressure, efficiency, torque and hydraulic power was investigated. Comparing design prediction with numerical CFD validation leads to a precise and extensive analysis. The validity of the used approach is demonstrated. Thus a qualitative prediction of flow characteristics for any axial-impeller at off-design is obtained.This allows for a in depth understanding of the fundamental working principles and consequences of the radial equilibrium equation at the design and also at off design points. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.extend

Grinding in an air classifier mill - Part I: Characterisation of the one-phase flow - Toneva, Petya Ivanova; Epple, Philipp; Breuer, Michael; Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2011)
In this and the related second paper [1], we present an in-depth study of the two-phase flow and the stressing conditions of particles in an air classifier hammer mill. This type of mill belongs to the mostly used mills at all. In order to develop a predictive grinding model not only the material's reaction to the applied stress but also the stressing conditions within the mill, e.g. impact velocity, incidence angle, number of stress events, have to be known. The latter are strongly affected by the interactions between the fluid and the solid phase within the mill. Systematic flow investigations in the vicinity of the impact elements and in the region of the internal classifier have been performed by Particle Image Velocimetry (PIV) and by numerical predictions of the fluid flow in the complete mill using a commercial CFD solver. Different pin geometries have been studied at various peripheral velocities of the grinding disk and the classifier. The classifier velocity does not influence the velocity profiles near the impact elements in the main flow direction and vice versa, the flow in the grinding zone has little influence on the classification. The velocity profile in front of the impact element, where the comminution process takes place, is constant with time and preserves a characteristic form independent of the operational conditions. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.grindi
Keywords: CFD; Comminution; Grinding; Impact mills; Multiphase flow; PIV

High efficiency design of high pressure radial fan spiraled casings used for biogas transport - Bleiziffer, Mihai; Epple, Philipp; Schmidt, Harald; Delgado, Antonio; Rußwurm, Hans (ASME 2009 International Mechanical Engineering Congress and Exposition, IMECE2009, 2010)

High efficiency propeller design based on the Betz minimum induced loss condition and CFD validation on an APC 8'' propeller - Albert, Sven; Epple, Philipp; Grashof, Bettina; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2013)
Betz [1] described the wake flow conditions for a propeller of minimum induced loss. The condition is somewhat similar to the elliptic circulation distribution of a finite wing, which was found by Prandtl [2]. Larrabee [3] reworked the theory in his 1979 paper Practical Design of Minimum Induced Loss Propellers, allowing for a step by step design of a propeller of specified RPM, advance velocity, diameter and thrust. In the present work the Larrabee model was programmed in VBA utilizing MS Excel and applied to a series of selected propellers. The minimum induced loss condition can be met for a chosen propeller duty point only. In order to evaluate off design points the blade element theory according to Glauert [4] was applied and implemented in the design tool. The tool itself offers complete freedom over the propeller parameters, including the choice of blade sections. Also a geometry export function into the ANSYS curve format was implemented to allow for a fast CFD computation of the current propeller design. For theory evaluation purposes a commercially available RC model propeller with 8″ in diameter was chosen as a reference. This propeller is listed in the wind tunnel measurements database of the University of Illinois [5]. CFD computations of the reference propeller design showed very good agreement with the experimental data, therefore indicating an accurate CFD setup. The theory of minimum induced loss is based on the distribution of circulation along the propeller's blades, which was also investigated using CFD. Satisfying the minimum induced loss condition, several design strategies are shown and evaluated, ultimately leading to a design which proved to be superior to the actual reference design. Hence the validity of the loss condition could be shown. Also deep insights into the circulation along propeller blades were gained which in turn allow for a further refinement of theory and design tool. Copyright © 2013 by ASME.
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.highef

High pressure fan design for biogas plants - Epple, Philipp; Schmidt, Harald; Bleiziffer, Mihai; Delgado, Antonio; Rußwurm, Hans (ASME 2009 International Mechanical Engineering Congress and Exposition, IMECE2009, 2010)

Influence of surface tension and inner pressure on the process of fibre drawing - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (Journal of Lightwave Technology, 2010)
The present contribution deals with thermofluidynamical features occurring during the drawing of capillaries for microstructured optical fibres. Here, the process stability depends strongly on flow and thermal processes taking place as a preform is heated and drawn in the furnace. This is the case particularly for hollow fibres for which the existence of the inner hole directly depends on material parameters such as the surface tension and the rheological properties and on process parameter such as hole internal pressure and the process temperature. A fluid-mechanics model suggested in the literature that makes use of asymptotic analysis based on small aspect ratio of the micro capillaries, has been revisited and improved recently and the leading-order equations have been then examined in some asymptotic limits by Luzi et al.. Starting from the novel class of solutions of the simplified equations of motion the present paper focuses on the effect of both surface tension and internal hole pressure since those are of essential importance during drawing. Thus, comparisons with experimental data are performed, in order to validate the analytical model developed in , which will be briefly presented here. The theoretical model gives very accurate predictions both when the internal hole is pressurized or when no pressure is applied, as long as the temperature does not reach too high values. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.influe
Keywords: Asymptotic analysis; Holey fibres; Micro structured optical fibres (MOFs); Numerical methods; Photonic crystal fibres

Inverse analytical and computational design method applied to a low pressure axial fan - Bleiziffer, Mihai; Epple, Philipp; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2010)
Nowadays precise and reliable tools for designing and optimizing turbomachines have a high impact on industrial and research fields. The design methods of turbomachines follow usually two main paths: direct design, where performances are achieved by iteratively modifying a given geometry, and inverse design where performance characteristics are prescribed and the proper geometry for reaching them is found (usually using analytical methods). Both of these methods are used today in research and development and they are coupled with numerical simulations (CFD) for shorter design cycles. This paper proposes an inverse design approach for low pressure axial fans based upon performance equations, namely the equations for total-to-static pressure and efficiency. To validate our approach we use numerical simulation of the axial fan in a virtual test rig. Combining inverse design with the CFD for its validation offers an integrated approach for improving the design in the development phase. In the first step analytical energy equations are derived for a blade cascade section and then integrated over the blade surface, i.e. from hub to tip radii, providing a dependency of the theoretical performances characteristics such as for the pressure and the efficiency, as a function of the flow-rate, rotating speed and the outer dimensions and blade angles of the machine. The next step computes inversely the main outer dimensions and blade angles of the geometry required for reaching the performance. In the final design step the blade shape is computed inversely using a NACA 4 Digit camber as it will be shown in the paper upon the required blade angles and other constrains of the cascade. The final shape is generated in CAD software-program and then a proper computational grid is generated so that it can be finally simulated with a commercial Navier-Stokes solver for the complete pressure and efficiency characteristics. The aim of this study is to offer general conclusions about the analytical influence of certain geometry parameters on the design and optimization of axial fans of this type. The last step for the proposed design method is typically the experimental validation with prototypes which will be not covered in this study. Copyright © 2010 by ASME.
UnivIS-Import:2017-01-09:Pub.2010.tech.ITC.stmmec.invers

Jet printing of colloidal solutions - Numerical modeling and experimental verification of the influence of ink and surface parameters on droplet spreading - Schneider, Olga; Epple, Philipp; Teuber, E.; Meyer, Bernhard; Jank, M. P. M.; Rauh, Cornelia; Delgado, Antonio (Advanced Powder Technology, 2011)
Ink jet printing of functional materials promises an efficient route for the manufacturing of future low cost and large-area electronics applications. The effect of capillary flow of thin liquid films, the control of droplet spreading by suitably influencing the wetting properties of surfaces, the rheology of the ink and the process design play a relevant role in improvement of ink jet printed patterns. This work presents the experimentally based numerical study of the shape of single ink jetted droplets controlled by homogeneous contact angle distributions. The dynamics of the fluid on the substrate surface is treated in the frame of the lubrication theory using the concept of a precursor film and modeling the equilibrium contact angle by a disjoining pressure. The model describes the spreading of axisymmetric droplets considering different material and process parameter configurations. It is shown that the spreading process can be modeled separately from the drying process within a certain range of contact angles.
EAM Import::2019-03-12

Numerical solution and experimental validation of the drawing process of six-hole optical fibers including the effects of inner pressure and surface tension - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Rauh, Cornelia; Fujimoto Meinecke, Ken; Delgado, Antonio (Journal of Lightwave Technology, 2012)
Microstructured optical fibers (MOFs) achieve their desired performance via a pattern of holes that run trough the whole length of the fiber. The variation of the hole pattern allows the production of a variety of optical effects. However, the cross-sectional hole structure can be different from that designed in the preform, due to the combined effects of surface tension and internal pressure. The present paper focuses on the comparison between experiments and numerical calculation of a six hole-optical fiber taking into account the effects of surface tension and internal hole-pressure, since those are of essential importance during drawing. It is shown that the numerical computations deliver reliable results for practical applications and can be used as a predictive tool for fiber development, as long as the inner pressure or the temperature do not exceed too high values. © 2012 IEEE.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.numeri
Keywords: Hley fibers; microstructured optical fibers (MOFs); nmerical modelling; numerical methods; photonic crystal fibers

Parmeterization of the total pressure distribution along a low-pressure axial fan blade according to the design requirments - Pascu, Maria; Epple, Philipp; Delgado, Antonio; Durst, Franz (2008 ASME International Mechanical Engineering Congress and Exposition, IMECE 2008, 2009)
Keywords: Blade profile; Non - free vortex flow; Design strategy; Optimum pressure distribution

Performance optimization method for radial fans with combined vaneless circular and volute diffusers applied to an industrial fan - Epple, Philipp; Miclea, Mihai; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings, 2009)
The use of high speed radial impellers is very common for industrial fans and blowers. The aerodynamic design of these machines can be made through direct or inverse means. The design process is almost always direct, based on the existing impeller series and available experimental data [1]. This paper presents the design results and optimization of high speed radial impellers with combined vaneless radial and volute diffusers used for industrial fans, through a combined analytical - numerical method validated by measurements of prototypes at the test rig. The reduction of the velocity from the outlet of the impeller to the outlet of the vaneless diffuser and hence the velocity at the inlet of the volute has a significant influence on the turbulence intensity and hence on the noise and therefore was a major parameter in determining the outer diameter of the circular vaneless diffuser. The designs where then validated by means of CFD computation, and following the numerical results, prototypes for both the volute and the impeller were built and experimentally investigated. The experimental results confirmed the numerical ones and it was shown that the optimized impeller had an absolute increase in efficiency with 70% at the operating point. One has to mention, that in this design, because of the special medical application, the operating point has to be unusually chosen shifted from the maximum efficiency. The results presented show the potential and advantages of the combined analytical and numerical method suited to perform a coupled design of high efficiency radial impellers and spiral casings. It shows also that new designs and improvement of existing designs are possible without the need of a previous impeller series or knowledge of experimental data. Copyright © 2008 by ASME.
UnivIS-Import:2015-04-16:Pub.2009.tech.ITC.stmmec.perfor

Prediction of the flow characteristics of an axial fan at off design - Semel, Matthias; Epple, Philipp; Litfin, Oliver; Grashof, Bettina; Delgado, Antonio (Proceedings of the Conference on Modelling Fluid Flow, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.predic_3

Radial impeller design optimization matched for high efficiency fans - Epple, Philipp; Semel, Matthias; Smith, Henrik; Litfin, Oliver; Delgado, Antonio (ASME 2011 International Mechanical Engineering Congress and Exposition (IMECE 2011), 2011)
Radial fans and blowers are widely used in many different fields, such as heater blowers or fans and blowers for vacuum cleaners. Although the impellers for these fans are already quite well optimized, it is possible to increase the efficiency of the fan matching the impeller properly to it. A very common fan optimization strategy is to increase the efficiency of the radial impeller, keeping its operating point, i.e. the flow rate of maximum efficiency. However, in most of these cases the impeller is not matched to the fan and hence this procedure will not deliver the best fan, even if the efficiency of the impeller is improved. In order to understand how an optimization of the fan has to be done, a theoretical treatment is presented. Detailed theoretical formulas are presented and discussed. In order to validate the theory, a series of well directed impellers and fans was designed, CAD models constructed and using ANSYS CFX finally the corresponding flow simulation was performed. It is shown how the impellers have to be modified in order to shift the flow rate of maximum efficiency without significant decrease in efficiency. Finally a detailed experimental study was performed at the test rig conforming the German engineering norm DIN 24 163 [1]. Here the theoretical achievements were systematically verified at the test rig for vacuum cleaner fans. It is shown how to, based on this theory, from the very beginning design the radial impellers such that they are perfectly matched to the full fan. In such a way it is shown how to increase the efficiency of radial fans and blowers substantially. Copyright © 2011 by ASME.
UnivIS-Import:2015-04-16:Pub.2011.tech.ITC.stmmec.radial
Keywords: CFD; Impeller-system matching; Radial impeller design

Study of the effects of inner pressure and surface tension on the fibre drawing process with the aid of an analytical asymptotic fibre drawing model and the numerical solution of the full N.-St. equations - Luzi, Giovanni; Epple, Philipp; Rauh, Cornelia; Delgado, Antonio (Archive of Applied Mechanics, 2013)
Micro-structured optical fibres (i.e. fibres that contain holes) have assumed a high profile in recent years and given rise to many novel optical devices. The problem of manufacturing such fibres by heating and then drawing a preform is considered for the case of annular capillaries. A fluid mechanics model suggested in the literature that uses asymptotic analysis based on the small aspect ratio of capillaries has been compared with the full 3D set of the N.-St. equations, for modelling the fabrication of capillaries. The final asymptotic equations, analysed in some asymptotic limits, are solved numerically and then compared with the N.-St. solutions, obtained with a commercial finite elements solver. These asymptotic limits give valuable practical information about the control parameters that influence the drawing process, taking into account the effects of surface tension and inner pressure, since those are of essential importance during drawing. It is shown that the asymptotic method delivers reliable results as long as the inner pressure does not exceed too high values. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.tech.ITC.stmmec.studyo
Keywords: Asymptotic analysis; Holey fibres; Mathematical modelling; Micro-structured optical fibres (MOFs); Numerical methods; Photonic crystal fibres

System matched 3D radial impeller design with variable inlet angle distributions - Semel, Matthias; Smith, Henrik; Epple, Philipp; Litfin, Oliver; Delgado, Antonio; Pfannschmidt, Klaus; Grobeis, Detlev (Proceedings of ASME Turbo Expo 2012, 2012)
In vacuum cleaners radial impellers with high rotational speed are very often used. A high rotational speed is connected with a best efficiency point of the radial impeller at a high flow rate. This is contrary to the working point of the whole system. Thus there is need for a radial impeller designs having a high efficiency at low flow rates under the restriction of a high rotational speed. One important parameter connected to the hydraulic efficiency characteristics of the radial impeller is the blade inflow angle b1. In order to shift the best efficiency point towards lower flow rates radial impellers with double curved blades and a linear b1 distribution were designed and CFD simulations were done in order to investigate the effect of this approach. A linear variation of the inflow angle b1 enables the designer to shift the efficiency characteristics of the impeller towards lower flow rates with a gain in hydraulic efficiency and pressure increase. Copyright © 2012 by ASME.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.system

The flow field in the mill - a key factor for the prediction of the comminution result - Epple, Philipp; Breuer, Michael; Peukert, Wolfgang; Toneva, Petya Ivanova; Wirth, Karl-Ernst (AIChE Annual Meeting, Conference Proceedings, 2006)
Measurements of the mean and time dependent velocity profile were obtained for the first time in an air classifier mill using particle image velocimetry (PIV). Detailed measurements in the vicinity of the impact elements and in the region of the internal classifier are presented. Different pin geometries have been studied at various circumferential velocities of the grinding disk and the classifier. Regions with high turbulence have been observed for all investigated pin geometries at the flow off side of the impact element. The classifier velocity doesn't influence the velocity profiles near the impact elements in main flow direction. The velocity profile on the front sight of the impact element, where the comminution process takes place, is constant with time and preserves a characteristic form with varying operational conditions. The one phase flow field in the complete mill geometry has been modelled by CFX.
UnivIS-Import:2015-04-16:Pub.2006.tech.ITC.stmmec.theflo
Keywords: Air classifier mill; CFX; Flow investigations; PIV; Turbulence modeling

The impact of the gas temperature and of the relative humidity on the performance of fans operating in drying plants - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (ASME 2018 International Mechanical Engineering Congress and Exposition, IMECE 2018, 2018)

Vortex Breakdown und Stallbeginn in einer Axialpumpe - Goltz, Isabel; Kosyna, Günter; Epple, Philipp; Delgado, Antonio (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.vortex